Has the Introduction of Bookbuilding Increased the Efficiency of China's IPO Pricing? - FEI, Jiehui (Institutional Knowledge at Singapore Management University, 2009)
Book-building is commonly adopted in global primary markets and regarded as the most efficient pricing method for accurate IPO pricing by literatures. China has introduced book-building in 2005 to increase IPO pricing accuracy and the capabilities of domestic institutional investors. However, with the current IPO data from China, I find the level of under-pricing has unexpectedly increased after book-building, which is against the empirical studies of a few domestic papers. Secondly, there's some evidence that with better information disclosure from issuer-side through book-building process, the signaling and ex-ante uncertainty effect that previously caused under-pricing has been reduced. But there're unique findings on both Shanghai and Shenzhen Stock Exchange due to the bull market effect, the launch of SME Board and the removal of IPO suspension after mid-2006. Last but not least, large number of institutional investors involved in book-building is likely to be regarded as a signal for herding behavior on China's secondary market and based on the information collected from book-building, underwriters tend to over-adjust final offer price.